Chemically induced oncogenesis in the peripheral nervous system is suppressed in congenic BDIX.BDIV-Mss1 and -Mss7 Rats - Kölsch, Bernd; Berg, Linda van den; Fischer, Christine; Winzen-Reichert, Bettina; Kutritz, Andrea; Kindler-Röhrborn, Andrea (G3: Genes, genomes, genetics, 2016)
Human malignant peripheral nerve sheath tumors (MPNSTs) are highly aggressive soft-tissue sarcomas with a poor prognosis that arise either in the context of neurofibromatosis 1 or sporadically. Inbred BDIX and BDIV rat strains highly susceptible and resistant, respectively, to the development of ethylnitrosourea-induced MPNST enable us to identify, by using methods not applicable in humans, variant alleles involved in the pathways underlying individual MPNST risk. On the basis of a genome-wide association analysis using reciprocal intercrosses of BDIX and BDIV, BDIV alleles of two loci on chromosome 10, Mss1 and Mss7, were predicted to lower the risk of MPNST, the latter locus with a female bias. In this study we confirm the two nonoverlapping loci by exposing two congenic strains, BDIX.BDIV-Mss1 (Mss1) and BDIX.BDIV-Mss7 (Mss7), each carrying a BDIV genomic segment spanning the respective locus, to ethylnitrosourea. Compared with BDIX rats, the rate of MPNST is reduced 6.2-fold and 2.0-fold for Mss1 and Mss7 rats of both sexes, respectively. Although a moderate gain of survival time (30−50 days) is seen in Mss1 rats of both sexes and Mss7 males, Mss7 females survive 134 days longer than BDIX females. BDIV alleles at Mss7 obviously cause a markedly increased intrastrain sex difference regarding survival time in Mss7 compared with BDIX rats. Fine mapping will lead to the identification of allelic variants modulating rat MPNST risk and subsequently to their human counterparts. This is of particular relevance, because so far neither gene nor anonymous sequence variants have been identified that influence the risk of human sporadic Schwann cell malignancy.
Gesehen am 29.04.2020